Complementary and alternative medicine modalities used to treat adverse effects of anti-cancer treatment among children and young adults: a systematic review and meta-analysis of randomized controlled trials - Dana C. Mora; Grete Overvåg; Miek C. Jong; Agnete E. Kristoffersen; Debbie C. Stavleu; Jianping Liu; Trine Stub (BMC, 2022)
Abstract Background Dealing with the symptom burden of cancer diagnosis and treatment has led parents to seek different self-management strategies including Alternative and Complementary Medicine (CAM). The aim of this study was to perform a systematic review and meta-analysis about the use and effect of CAM modalities to treat adverse effects of conventional cancer treatment among children and young adults. Methods Six scientific research databases were used to identify randomized controlled trials (RCTs) from 1990 to September 2020. Included studies investigated the use of CAM to treat cancer treatment related adverse effects in children and young adults compared to controls. Results Twenty RCTs comprising 1,069 participants were included in this review. The included studies investigated acupuncture, mind-body therapies, supplements, and vitamins for chemotherapy-induced nausea and vomiting (CINV), oral mucositis, and anxiety among children and young adults who underwent conventional cancer treatment. Seven studies (315 participants) were included in the meta-analysis. The overall effect of CAM (including acupuncture and hypnosis only) on chemotherapy-induced nausea and/or vomiting and controls was statistically significant with a standard mean difference of -0.54, 95% CI [-0.77, -0.31] I2 = 0% (p < 0.00001). There was a significant difference between acupuncture and controls (n = 5) for intensity and/or episodes of CINV with an SMD -0.59, 95% CI [-0.85, -0.33] (p < 0.00001). No significant difference was found between hypnosis and controls (n = 2) for severity or episodes of CINV with an SMD -0.41, 95% CI [-1.09, 0.27] I2 = 41% (p = 0.19). Conclusion Current evidence from this meta-analysis of randomized controlled trials shows that CAM, including acupuncture and hypnosis only, is effective in reducing chemotherapy-induced nausea and vomiting in children and young adults. More rigorous trials and long-term effects should be investigated if acupuncture and hypnosis are to be recommended for clinical use.